1996
DOI: 10.1007/bf01788841
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the psychiatric management and outcome of delirium in the cancer patient

Abstract: This report describes the evaluation and treatment of delirium in the cancer patient in a major comprehensive cancer center. Ninety consecutive cases of delirium seen by the inpatient psychiatry consultation/liaison service were analyzed in a retrospective fashion to evaluate demographic information, alcohol use, central nervous system disease, coexisting medical disease, and past psychiatric history. Delirium cases were divided into hyperalert, hypoalert, and mixed subtypes. For these three subtypes, medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 40 publications
0
48
1
Order By: Relevance
“…23,24 It has been suggested that the subtypes differ in the underlying pathology, response to therapeutic intervention and outcome, with hypoactive delirium having a notably poorer prognosis although some studies have not found such an association. 25,26 Hypoactive delirium is likely to go undiagnosed thereby resulting in poorer prognosis. Hyperactive delirium is preferentially referred for management by psychiatrist because of disturbed behavior, disorientation, irrelevant talk and decreased sleep.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 It has been suggested that the subtypes differ in the underlying pathology, response to therapeutic intervention and outcome, with hypoactive delirium having a notably poorer prognosis although some studies have not found such an association. 25,26 Hypoactive delirium is likely to go undiagnosed thereby resulting in poorer prognosis. Hyperactive delirium is preferentially referred for management by psychiatrist because of disturbed behavior, disorientation, irrelevant talk and decreased sleep.…”
Section: Discussionmentioning
confidence: 99%
“…According to the available literature, the evidence linking these 2 classes of medications to delirium seems to be weaker than that for opioids, 3 although all 3 groups of medications are plausible risk factors from a biologic standpoint. 30 Benzodiazepines and corticosteroids have been associated with delirium in case series [31][32][33][34] (a rather weak study design). 35 In cohort and case-control studies, no significant associations were identified between corticosteroids and delirium, whereas benzodiazepines were associated significantly with delirium in 1 study.…”
Section: Discussionmentioning
confidence: 99%
“…Among those studies, the results are confl icting. The hyperactive subtype was more common in two studies [9,11] , the hypoactive subtype was more frequent in one study [12] and the mixed subtype was more frequent in three studies [7,8,13] . There is only one study on delirium in the elderly, showing that the hypoactive subtype was the most frequent subtype of delirium [12] .…”
Section: Incidence Clinical Features and Subtypes Of Delirium In Eldmentioning
confidence: 99%